Ted - DiTerlizzi, Tony (New York : Simon & Schuster Books for Young Readers, 2001)
A young boy manages to get his busy father's attention with the help of a special imaginary friend.
Keywords: Imaginary playmates -- Fiction; Father-son relationship -- Fiction